Testing TCP Westwood+ over Transatlantic Links at 10 Gigabit/Second rate - Saverio Mascolo; G. Racanelli (Proceedings of the 3rd International Workshop on Protocols for Fast Long-Distance Networks, 2005)
Recent introduction of 10 Gigabit routers and 10 Gigabit Ethernet cards makes the issue of designing and testing new protocols capable of efficient utilization of 10 gigabit Internet paths particularly important. In this work we report a first investigation of the performance of Westwood+ TCP over large-delay paths at 10 gigabit/second rates. The investigation has been conducted at the CERN–IT division using the implementation of Westwood+ we have recently made available in the Linux 2.6 stack. The main feature of Westwood+ TCP is its adaptive setting of the control windows after a congestion episode obtained by estimating the bandwidth available along the connection path. The ‘‘Westwood+ feature’’ has been proven to be particularly effective over lossy channels, where packet losses are not due to congestion, and to improve fairness. Experimental results reported in this work show that remarkable throughput and fairness improvements are also present in the presence of very high bandwidth-delay-product paths. In the future, we plan to combine the way Westwood+ sets the control window after congestion with modifications of the standard TCP probing phase. A first attempt in this direction is also reported in this paper.
February 3–4, 2005, École Normale Supérieure